Investigation of Printing‐Based Graded Bulk‐Heterojunction Organic Solar Cells. Issue 4 (12th March 2015) - Bottenfield, Christian G.; Wei, Fanan; Park, Hui Joon; Guo, L. Jay; Li, Guangyong
Abstract: A 2‐step method involving the evaporation of solvent through surface encapsulation and induced alignment (ESSENCIAL) has been used to create a compositionally graded active layer of interspersed acceptor and donor domains by printing‐based technologies, which can be used to fabricate solar cells with higher performance than that from traditional bulk heterojunction fabrication methods. Herein, to clarify the fundamental mechanism of the performance improvement, a multi‐scale simulation has been conducted to compare solar cells resulting from these two types of processing. The multi‐scale simulation identified the underlying improvements of the ESSENCIAL morphology over traditional morphologies. Monte Carlo simulations obtained higher hole‐mobility values and lower monomolecular recombination rates for the ESSENCIAL‐fabricated cells that, in conjunction with the optical and electrical components, showed higher short‐circuit currents, fill factors, and efficiencies, as indicated experimentally. The simulation offers the unique ability to model the varied active layer compositions and elucidate the underlying solar cell physics of complex morphologies. Abstract : Explaining the physics: A multi‐scale simulation composed of optical, Monte Carlo, and electrical simulations is used to identify and understand the improvements of a new, printing‐based morphology for organic solar cells. Organic solar cells with normal bulk‐heterojunction morphologies and the new printing‐based morphologies are simulated and compared to identify the latter's fundamental improvements.